2022
DOI: 10.3389/fvets.2021.800388
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Utilizing Non-replacement Male Calves in the Australian Dairy Industry: A Qualitative Study

Abstract: Male non-replacement calves in dairy systems represent an underutilized economic resource for dairy producers worldwide. Despite this, increasing the practice of rearing non-replacement male calves has significant barriers both in on-farm adoption and practice. Poor neonatal rearing practices, higher levels of morbidity and mortality, and disaggregated production pathways with multiple points of handling, have all been described as barriers to adoption of surplus calf production. To identify the critical decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The questionnaire design was built on previous qualitative findings described by Vicic et al ( 8 ) who identified attitudes and practices surrounding on-farm non-replacement male calf production, euthanasia practices, and producer wellbeing. Through mixed methods research strategies, the outcomes from the qualitative interviews informed the directive of each item developed for the online questionnaire presented in this study ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The questionnaire design was built on previous qualitative findings described by Vicic et al ( 8 ) who identified attitudes and practices surrounding on-farm non-replacement male calf production, euthanasia practices, and producer wellbeing. Through mixed methods research strategies, the outcomes from the qualitative interviews informed the directive of each item developed for the online questionnaire presented in this study ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite advances, these production pathways are often disaggregated in relation to intensive labor requirements, onfarm calf rearing facilities, and low-value saleable markets. This is also seen in dairy production systems in America and Canada, where similar issues have led to poor calf welfare and lack of adoption of on-farm rearing (7,8). A shift has occurred in societal attitudes towards the practices surrounding nonreplacement male calves and the need to identify alternative strategies to rear, process, and market a viable and economically sustainable dairy beef product.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…surplus locally" (F7P2). Australian dairy producers have expressed the desire to access improved markets for surplus calves, and producers who reported having well-established sale options had more success in selling their calves (Vicic et al, 2022). Proposals of alternative rearing options for surplus dairy calves in the United Kingdom have suggested the increased use of these calves for beef production (Rutherford et al, 2021).…”
Section: Care and Management Practicesmentioning
confidence: 99%